The Alzheimer’s Disease Cooperative Study – Activities of Daily Living dependence score: revision and validation of an algorithm evaluating patient dependence across the spectrum of AD severity - Chandler, Julie M.; Lansdall, Claire J.; Ye, Wenyu; McDougall, Fiona; Belger, Mark; Toth, Balazs; Mi, Xiaojuan; Sink, Kaycee M.; Atkins, Alexandra S. (Journal of Prevention of Alzheimer's Disease, The, 2025)
Increasing dependence on informal and formal caregivers in Alzheimer’s disease (AD) contributes to high societal cost. Treatments that delay time to increased dependence/care needs would be clinically meaningful, but these outcomes are rarely collected in early AD clinical trials. The 2015 ADCS-ADL dependence algorithm was created to estimate level of dependence in AD. To revise the original dependence algorithm to improve accuracy of dependence scores (DS) across AD severity, including early symptomatic AD. Secondary data analysis Community cohort; randomized clinical trial 14,000 participants enrolled across GERAS-EU observational study and 12 AD clinical trials. Three-phase algorithm revision: 1) reassess ADCS-ADL items to identify those appropriate for assessing dependence; 2) (a) assign individual item responses to degrees of assistance and (b) to operationalize assignment of DS based on extent of total assistance needed; and 3) validate revised algorithm in multiple datasets across AD severity from mild cognitive impairment due to AD to moderate-severe AD. The revised DS (0-6) algorithm classified most participants with early symptomatic AD as independent or moderately independent (DS<3) at baseline. With disease progression over time, the proportion of participants who were mildly to fully dependent (DS≥3) increased across AD severity. Increased DS was associated with incremental worsening of clinical outcomes. The revised ADCS-ADL DS algorithm provides a supplementary approach to evaluate the impact of emerging treatments on independence/care needs in AD and may be useful in clinical trials where the ADCS-ADL has been collected. EXPEDITION 1 NCT00905372; EXPEDITION 2 NCT00904683; EXPEDITION 3 NCT01900665; AMARANTH NCT02245737; TRAILBLAZER-ALZ NCT03367403; TRAILBLAZER-ALZ 2 NCT04437511; GRADUATE I NCT03444870; GRADUATE II NCT03443973; CREAD NCT02670083; CREAD 2, NCT03114657; TAURIEL NCT03289143; LAURIET NCT03828747